PENGARUH MODEL PEMBELAJARAN SAVI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTS MA CIKALIUNG - Nenden Suciyati Sartika; Septiani Dwi Arifiyanti; Ina Ramadina (Jurnal Math-UMB.EDU, 2020)
Mathematics is the science that underlies the development of modern technology and has an important role in various disciplines. The development of science and technology in the current era of globalization uses a mathematical mindset. Therefore, mathematics is a subject that must be studied at each level of the education unit. This study aims to determine whether or not there is a significant influence on the use of SAVI learning models on the mathematical communication skills of students at MTs MA Cikaliung. The method used in this study is a quasi-experimental method. Sampling was done by simple random sampling technique with a population of 89 students, and the sample used was 62 students from class VIII A as the experimental class and VIII B as the control class. The research instrument used in the form of a test essay (essay) is made based on indicators of mathematical communication skills. Based on data analysis using the t-test test method to test the proposed hypothesis, the results obtained with the value (tcount = 7.61> ttable = 1.67) at a significance level of 5%, then H0 is rejected and accept H1, so it can be concluded that there is Significant influence of the use of the SAVI learning model on mathematical communication skills of MTs MA students in Cikaliung.Keywords: Somatic, Auditory, Visualization, Intellectually, Mathematical Communication Skills.